2016
DOI: 10.18632/oncotarget.7050
|View full text |Cite
|
Sign up to set email alerts
|

The effect of HMGB1 on the clinicopathological and prognostic features of non-small cell lung cancer

Abstract: Several studies have assessed the diagnostic and prognostic values of high mobility group protein box 1 (HMGB1) expression in non-small cell lung cancer (NSCLC), but these results remain controversial. The purpose of this study was to perform a meta-analysis of the gene microarray analyses of datasets from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) to evaluate the association of HMGB1 expression with the clinicopathological and prognostic features of patients with NSCLC. Furthermore, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 46 publications
(37 reference statements)
2
56
0
Order By: Relevance
“…Moreover, HMGB1 was negatively related to the clinical and pathological characteristics of endometrial cancer. In the current study, the elevated expression levels of HMGB1 in both tissues and sera of patients are more commonly found in solid tumors, including hepatocellular,23 ovarian,24 colorectal25 and non-small cell lung cancers 26. The overexpression of HMGB1 was positively correlated with the prognosis of patients with various types of cancer 27.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, HMGB1 was negatively related to the clinical and pathological characteristics of endometrial cancer. In the current study, the elevated expression levels of HMGB1 in both tissues and sera of patients are more commonly found in solid tumors, including hepatocellular,23 ovarian,24 colorectal25 and non-small cell lung cancers 26. The overexpression of HMGB1 was positively correlated with the prognosis of patients with various types of cancer 27.…”
Section: Discussionmentioning
confidence: 55%
“…HMGB1 and HMGB2 are overexpressed across a large number of cancer types (TCGA data; http://www.cbioportal.org/; Gao et al, 2013), and HMGB1 overexpression has been directly linked to the proliferative capacity and metastasis of malignant cells (Tang et al, 2010) and of lung adenocarcinoma in particular (Feng et al, 2016). Hence, we sought to investigate how HMGB2mediated deregulation of chromosome organization might affect lung adenocarcinoma patient lines.…”
Section: Hmgb1 and B2 Control The Proliferative Capacity Of Lung Adenmentioning
confidence: 99%
“…Anti-HMGB1 Antibody Extracellular HMGB1 Leukemia [8] Ethyl Pyruvate Extracellular HMGB1 Hepatocarcinoma [11] Glycyrrhizin Extracellular HMGB1 Melonoma [8] Oxaliplatin Intracellular HMGB1 Colon Carcinoma [12,13] Quercetin Extracellular HMGB1 Breast Cancer [9] HMGB1 in NSCLC As the previous studies showed, HMGB1 over expressed in NSCLC and affected the prognosis and development of NS-CLC patients. Because of the rare mutation of HMGB1 in NSCLC patients [3] , we considered HMGB1 as a better targeting bio-marker for NSCLC than TKs. However, there's no research target HMGB1 as a therapy strategy for treatment of NSCLC patients.…”
Section: Targeting-hmgb1 Location Tumor Types Referencesmentioning
confidence: 99%
“…A major part of researches have revealed that over expression of HMGB1 triggers cell differentiation, cell migration and cancer metastasis after being release into the extracellular space, thus it could promote cancer development and resistance [2] . Our previous study has already showed that HMGB1 over expressed in NSCLC and intensely affect the survival of NSCLC patients [3] , so this review focused on the therapeutic target value of HMGB1 for NSCLC in current researches.…”
Section: Introductionmentioning
confidence: 99%